Labor market integration of German immigrants and their children: Does personality matter? - Anna-Elisabeth Thum (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Educational attainment, length of stay, differences in national background and language skills play an acknowledged important role for the integration of immigrants. But integration is also a social process, which suggests that psychological factors are relevant. This paper explores whether and to what extent immigrants and their children need to believe in their ability to control their own success. To quantify this personal trait I use a measure of an individuals sense of control overoutcomes in life - such as finding a job. This measure is known in psychology as "the locus of control". I first estimate an exogenous measure. Then I address the problem that this measure is actually endogeneous in a labor market outcomeequation by employing a model in which the sense of control is an endogenized latent factor in a simultaneous equation model. The determinants of this sense of control as well as its effect on the probability of being employed are examined. The model is estimated using a Bayesian Markov Chain Monte Carlo algorithm. Results with endogenized personality indicate that, on average, immigrants believe less than natives in being able to control outcomes in life, but children of immigrants have already a stronger sense of control than their parents. The paper also finds that sense of control over lifes outcomes positively contributes to the probability of being employed. This means that immigrants and their children face a double disadvantage on the labor market: they are disadvantaged because of their status as an immigrant and they have a lower sense of being able to control their situation, which is a personality trait that matters on the labour market.
Keywords: 330